NILAI-NILAI PENDIDIKAN KARAKTER DALAM TARI LEGONG NGEWAYANG (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
Legong Ngewayang is a new creation of palegongan dance which is danced by 8 dancers. This palegongan creative dance is a traditional palegongan dance which uses movements that are thick with traditional movements, wrapped with new creative movements, arranged in such a way as to suit the needs of the dance. The Legong Ngewayang dance uses fans and puppets as props. This dance cannot be separated from the standards of traditional Pelegongan dance movements without eliminating the aesthetic forms of Balinese traditional dance such as: batel maya, pepeson, pengawak, pecet, pengrangrang and pekaad. This dance visualizes four clown characters consisting of wayang Tualen, wayang Merdah, wayang Delem and wayang Sangut. This research examines further the